Análisis de vulnerabilidades de las aplicaciones Android utilizadas en gestión de empresas. - Putan Santillán, Jesús Alejandro (2023)
Information security is crucial for mobile users as the applications they use may contain sensitive personal information. Security vulnerabilities can vary depending on the platform or application, and there are concerns about possible attacks from different fronts, the use of insecure Android applications can have serious consequences for the security and privacy of the company, its productivity and reputation. The objective of this work is to carry out a vulnerability analysis of Android applications used in business management. This document was crucial and justifiable, since it is important to carry out studies on the vulnerabilities of Android applications used in the commercial management of companies. These applications represent potential risks and it is essential to analyze critical situations of mobile technologies to minimize the risks associated with their use; It was critical to develop strong security strategies and measures to protect mobile devices and encourage the use of secure and trusted applications. Regarding the methodology used, it is important to select an appropriate methodology. Common ones include case studies, interviews with experts, and document analysis. A qualitative methodology will be used to understand subjective perceptions and behaviors. This methodology focuses on the analysis of textual and visual data to identify patterns and themes. The interview instrument will be used to collect data from experts in systems and business management, compare results and discuss contributions. This document concludes that vulnerabilities in Android applications used in company management can have serious consequences for the security, productivity and business continuity of companies. Developers must implement adequate security measures to protect applications and users must take measures to protect their devices and personal data.